Dementia risk among individuals with a migrant background—a scoping review - Wittmann, Felix; Luppa, Melanie; Thyrian, Jochen René; Hoffmann, Wolfgang; Riedel-Heller, Steffi G. (Frontiers in Dementia, 2025)
BackgroundWhile non-pharmacological dementia prevention is increasingly prioritized in research and policy, intersectional perspectives remain underrepresented. These are essential to address structural determinants of health and persistent diversities and inequities. This scoping review aimed to synthesize the existing amount of research on dementia risk and prevention in relation to migration background, focusing on three questions: (1) dementia risk and associated risk factors, (2) prevention, and (3) evidence concerning the most marginalized migrant populations.MethodsA systematic search was conducted in PubMed, PsycInfo, and Web of Science following PRISMA guidelines. The Population-Concept-Context (PCC) framework was used to define inclusion and exclusion criteria. Two researchers independently screened abstracts and full texts; discrepancies were resolved through discussion with a third reviewer. The included studies were synthesized and discussed.ResultsThirty-nine studies met the inclusion criteria for (1), including some known risk factors and relevant migration background factors, such as language barriers, discrimination, and mental health. Regarding prevention (2), only a few studies addressed migration-related aspects, including faith, internet use, or diagnosis. Evidence on asylum seekers, undocumented individuals, or those with irregular status was absent (3).ConclusionThis review highlights significant knowledge gaps in dementia research concerning people with a migrant background. However, risk and preventive factors were summarized and partially combined regarding targeted, sensible prevention. Nevertheless, migration might modify dementia risk across multiple levels, yet preventive efforts remain sparse. Addressing these gaps is essential to designing equitable strategies for reducing dementia risk and inclusive implementation in research and practice.Systematic review registrationidentifier: OSF.IO/YHVAW.